Food Thought Suppression Inventory: Test–retest reliability and relationship to weight loss treatment outcomes. (August 2016) - Barnes, Rachel D.; Ivezaj, Valentina; Grilo, Carlos M.
Abstract: This study examined the test–retest reliability of the Food Thought Suppression Inventory (FTSI) and its relationship with weight loss during weight loss treatment. Participants were 89 adults with and without binge eating disorder (BED) recruited through primary care for weight loss treatment who completed the FTSI twice prior to starting treatment. Intra-class correlations for the FTSI ranged from .74–.93. Participants with BED scored significantly higher on the FTSI than those without BED at baseline only. Percent weight loss from baseline to mid-treatment was significantly negatively correlated with the FTSI at baseline and at post-treatment. Participants reaching 5% loss of original body weight by post-treatment had significantly lower FTSI scores at post assessment when compared to those who did not reach this weight loss goal. While baseline binge-eating episodes were significantly positively correlated with baseline FTSI scores, change in binge-eating episodes during treatment were not significantly related to FTSI scores. The FTSI showed satisfactory one week test–retest reliability. Higher levels of food thought suppression may impair individuals' ability to lose weight while receiving weight loss treatment. Highlights: Food Thought Suppression Inventory (FTSI) had satisfactory test–retest reliability. At baseline, there were no sex differences in FTSI scores. At baseline, FTSI scores were associated positively with binge eating. FTSI scores were unrelated to changes in binge-eating frequency during treatment. Weight loss was associated with less reported food thought suppression.